The Impact Of Anthropogenic Pressure On The Change Of Water Relations In Gardno-Łeba Lowland - Chlost, Izabela; Sikora, Magda (Quaestiones Geographicae, 2015)
This article presents an analysis of cartographic materials of the 19th and 20th centuries in terms of changes in the surface water network of the Gardno-Łeba Lowland. The obtained results confirmed that the natural water network was slightly transformed in the first half of the 19th century and considerably increased in the 20th century as a result of agricultural drainage system, especially drainage of wetlands, and river regulations. As a consequence, a hydrographic system with a forced water circulation has developed, that is quite different from the natural. On the one hand, it has become the reason for reversing the proportion in which the groundwater resources have been depleted, along with an increase in the surface water network density, and on the other hand it has caused a change in land use.